Partial pressures of CO2 in epikarstic zone deduced from hydrogeochemistry of permanent drips, the Moravian Karst, Czech Republic - Jiří Faimon; Monika Ličbinská; Petr Zajíček; Ondra Sracek (Acta Carsologica, 2012)
Permanent drips from straw stalactites of selected caves of the Moravian Karst were studied during one-year period. A hypothetical partial pressure of CO2 that has participated in limestone dissolution, PCO2(H)=10-1.53±0.04, was calculated from the dripwater chemistry. The value significantly exceeds the partial pressures generally measured in relevant shallow karst soils, PCO2(soil)=10-2.72±0.02. This finding may have important implications for karst/cave conservation and paleoenvironmental reconstructions.